Extraction and Characterization of Cellulose from Agricultural Residues: Wheat Straw and Sugarcane Bagasse - Karn, Anup; Thakur, Sweta; Shrestha, Bindra (Journal of Nepal Chemical Society, 2022)
Wheat straw and Sugarcane bagasse are agricultural as well as industrial wastes rich in lignocellulosic components that can be extracted easily and used as a renewable source of energy. The main aim of this present work was to explore the alternative source of cellulose extraction using simple, fast, and eco-friendly conditions. The process involves NaOH degradation, acid hydrolysis, and bleaching using hydrogen peroxide as a bleaching agent. The extracted compound was analyzed by XRD and FTIR techniques. The XRD peaks obtained were specific to cellulose Iβ which is a crystalline allomorph with a monoclinic structure. The crystallite size of cellulose obtained from sugarcane bagasse was 10.51 nm which is larger than the size of cellulose obtained from wheat straw i.e 4.04 nm. Cellulose from sugarcane bagasse showed a crystallinity index of 51.84 % whereas wheat straw showed only 17.94 %. The yield was slightly higher in wheat straw than in sugarcane bagasse. FTIR analysis in sugarcane bagasse showed a characteristic peak at 3255.84 cm-1 which is shifted to 3340 cm-1 in the case of wheat straw. This peak is due to the vibration of the –OH group in both of the materials. However, both of the materials showed the vibration of the C-O-C bond at 1033 cm-1.